Signifikansi Pendidikan Seksual oleh Orang Tua terhadap Anak 7-12 tahun - Asmat Purba; Alon Mandimpu Nainggolan; Delpi Novianti (Sekolah Tinggi Teologi Transformasi Indonesia, 2023)
Abstract: Most parents think that talking about sex with family members, especially children, is taboo. Taboo because they are not used to it and are not trained. This article aims to find appropriate ways for parents to successfully conduct sexual education for their children who are still in elementary school. The research method used is descriptive qualitative, with a qualitative approach to literature research (library research). Through this research it was found that sex education in the middle of the family, sexual education for elementary school students, spiritual education for children in the family context can prevent and overcome children's sexual problems. Children are God's gift entrusted to the family. Before they become girls or adults, they are children under the care of their parents. The church needs to equip parents in the context of sexual education for children. Parents are very strategic in educating their children at home regarding sexual education so that they are not patronized by the media and pornographic films which cause them to misunderstand sexuality which results in falling into sexual sins, pregnancies outside of legal marriage and the possibility of various venereal diseases.Abstrak: Sebagian besar orang tua menganggap bahwa membicarakan seks kepada anggota keluarga, khususnya kepada anak-anak adalah tabu. Tabu karena belum terbiasa dan terlatih. Artikel ini bertujuan untuk menemukan cara yang tepat bagi para orang tua agar berhasil melakukan pendidikan seksual kepada anak-anak mereka yang masih duduk di Sekolah Dasar. Metode penelitian yang digunakan adalah kualitatif deskriptif, dengan pendekatan kualitatif studi literatur. Melalui penelitian ini ditemukan bahwa pendidikan seks di tengah keluarga, pendidikan seksual bagi siswa Sekolah Dasar, pendidikan rohani anak di konteks keluarga dapat mencegah dan mengatasi permasalahan anak di bidang seksual. Anak-anak adalah karunia Tuhan yang dipercayakan kepada keluarga. Sebelum mereka menjadi gadis atau dewasa, mereka adalah anak-anak di bawah pengasuhan orang tua. Gereja perlu melengkapi orang tua dalam rangka pendidikan seksual bagi anak. Orang tua sangat strategis mendidik anak usia di jenjang Sekolah Dasar di rumah perihal pendidikan seksual agar mereka tidak digurui oleh media dan film-film porno yang mengakibatkan mereka salah memahami seksual yang mengakibatkan kejatuhan ke dalam dosa seksual, kehamilan di luar pernikahan yang sah dan kemungkinan berbagai penyakit kelamin